The Wisdom Researchers and the Elephant: An Integrative Model of Wise Behavior - Glück, Judith; Weststrate, Nic M. (Personality and social psychology review, 2022)
This article proposes an integrative model of wise behavior in real life. While current research findings depend considerably on how wisdom is conceptualized and measured, there are strong conceptual commonalities across psychological wisdom models. The proposed model integrates the components of several existing models into a dynamic framework explaining wise behavior. The article first specifies which real-life situations require wisdom and discusses characteristics of wise behavior. The core proposition of the model is that in challenging real-life situations, noncognitive wisdom components (an exploratory orientation, concern for others, and emotion regulation) moderate the effect of cognitive components (knowledge, metacognitive capacities, and self-reflection) on wise behavior. The model can explain the situation specificity of wisdom and the commonalities and differences between personal and general wisdom. Empirically, it accounts for the considerable variation in correlations among wisdom measures and between wisdom measures and other variables. The model has implications for the design of wisdom-fostering interventions and new wisdom measures.